Geocritical perspectives on urban spaces against the background of cognitive approaches to language: mental spaces and conceptual blending - Dahm, Johannes (Porównania, 2024)
Geocriticism deals with the relationship between material, real as well as imagined and fictional (urban) spaces. Three premises are central to the theoretical framework of this interdisciplinary approach to literary analysis: spatio-temporality, transgressivity and referentiality. This article aims to approach the problem of referentiality and shed light to the relationship between representation (text) and referent (city) – between fiction and reality – taking cognitive linguistic models into account. For this purpose, two interlinked cognitive linguistic theories are used: “mental spaces” and “conceptual integration” (blending theory). On the basis of these theories, the article sketches a blend – a kind of third space (or: thirdspace) with emergent structure – into which elements of both the imagined and the real existing city are projected.